SVM based multilevel Z source matrix converter with reduced power devices - Raghuram M.; Kumar A.; Kumar P.N.; Reza M.M.; Singh S.K.; Wang C.; Al Jaafari K. (My University, 2025)
Multilevel ultra sparse matrix converter is a condensed form of multilevel indirect matrix converter for unidirectional power flow operation. The main feature of this converter delivers quality of input and output waveforms using reduced size of input low pass filter elements. The major limitation of this converter is voltage gain and number of power devices used. To overcome this limitations, two new topologies are proposed in this paper. Moreover modulation technique required to operate the proposed converter is also discussed. To validate the proof of concept for proposed converter, MATLAB simulation has been performed. © 2020 IET Conference Proceedings. All rights reserved.